Pathogenesis of overactive bladder and surgical treatment according to the Integral Theory Paradigm - Peter Petros (BMJ Publishing Group, 2021)
Overactive bladder (OAB is a definition by the International Continence Society (ICS). It comprises three symptoms, urge, frequency and nocturia. OAB is a major problem for up to 30% of women, more so for elderly women. OAB is generally assumed to be a paradigm, but it cannot meet the criteria of a paradigm, as its causation is said to be "idiopathic" (unknown) and is said to have no known treatment. In 1993, it was demonstrated that the sequence of events in urodynamically diagnosed detrusor overactivity (now "DO") was identical with what occurred in normal micturition, which led to the conclusion that frequency, urgency, nocturia were in effect, an uncontrolled but otherwise normal micturition. Data from a 1997 experiment indicated the control mechanism of the bladder was binary, either closed or open, regulated by a peripheral musculoligamentous system under cortical control. The Integral Theory paradigm's view of OAB is based on and is compatible with, ICS definitions and descriptions. The Integral Theory paradigm (ITP) views OAB pathogenesis as anatomical, caused by defects anywhere along the control mechanism pathway, but mainly damage in its weakest link, collagen defects in the peripheral musculoligamentous system. Specific tests to prove causation consist of mechanically supporting suspensory ligaments, pubourethral ligament (PUL) or uterosacral ligament (USL), "simulated operations"; PUL support prevents urine loss on coughing; USL support by inserting the lower blade of a bivalve speculum into the vagina diminishes urge and pain. The ITP specifies treatment of correctible causes: squatting-based exercises to strengthen the reflex pelvic muscles, ligament repair by plication for premenopausal women, slings for postmenopausal women.